Evolving Epidemiology, Improving Diagnostic Tests and Their Importance for the Correct Diagnosis of Histoplasmosis - Thomas E. Schmidt; Tarsila Vieceli; Lisandra Serra Damasceno; Sarah Kimuda; Alessandro C. Pasqualotto; Nathan C. Bahr (Journal of Fungi)
Histoplasmosis has traditionally been described as having discrete geographic areas of endemicity. Over the last few decades, it has become more and more clear that these areas are not accurate depictions of where histoplasmosis can occur. Our understanding of where histoplasmosis occurs has improved in recent years due to improving access to diagnostic testing and increased reporting as well as larger at-risk populations (HIV and non-HIV immune suppression) resulting in more cases. Although areas of relatively higher risk and case numbers certainly still exist, histoplasmosis has been observed in much of the world at this point. Our knowledge of the geographic distribution of histoplasmosis, though improving, remains incomplete. While diagnostic testing has traditionally been confined to visualization and/or culture in much of the world, antigen testing has emerged as an excellent tool. Unfortunately access to antigen testing has been inadequate for much of the world, but this has started to change in recent years and will likely change more dramatically in the near future, assuming ongoing positive developments in the area of lateral flow tests for antigen testing. In this review, we describe the current understanding of the geographic distribution of histoplasmosis, the current landscape of diagnostic testing, and the evolution of both areas with an eye towards the future.